2021
DOI: 10.1044/2020_ajslp-20-00252
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth for Dysphagia Across the Life Span: Using Contemporary Evidence and Expertise to Guide Clinical Practice During and After COVID-19

Abstract: Purpose Our aim was to critically review recent literature on the use of telehealth for dysphagia during the COVID-19 pandemic and enhance this information in order to provide evidence- and practice-based clinical guidance during and after the pandemic. Method We conducted a rapid systematized review to identify telehealth adaptations during COVID-19, according to peer-reviewed articles published from January to August 2020. Of the 40 articles identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…They felt that they needed to adapt their practices for tele-assessments, including less reliance on their own observations and heavier reliance on supplementary sources of information and parents for child assessments. Research has consistently shown that adaptations of clinical practices are required to support clients or patients via telehealth ( Malandraki, Arkenberg, Mitchell, & Malandraki, 2021 ; Waller et al, 2021 ), and assessments for some conditions such as chronic pain require additional involvement from the clients or patients (e.g., Perez, Niburski, Stoopler, & Ingelmo, 2021 ). A number of specific challenges related to telehealth delivery for autism assessments were identified by clinicians, including administration difficulties with eye contact being most challenging to assess.…”
Section: Discussionmentioning
confidence: 99%
“…They felt that they needed to adapt their practices for tele-assessments, including less reliance on their own observations and heavier reliance on supplementary sources of information and parents for child assessments. Research has consistently shown that adaptations of clinical practices are required to support clients or patients via telehealth ( Malandraki, Arkenberg, Mitchell, & Malandraki, 2021 ; Waller et al, 2021 ), and assessments for some conditions such as chronic pain require additional involvement from the clients or patients (e.g., Perez, Niburski, Stoopler, & Ingelmo, 2021 ). A number of specific challenges related to telehealth delivery for autism assessments were identified by clinicians, including administration difficulties with eye contact being most challenging to assess.…”
Section: Discussionmentioning
confidence: 99%
“…Service providers must now actively engage with the rapidly evolving technology, such as use of remote stethoscopes, 23 understand barriers and support access to technology, 21 and develop appointment-specific telehealth guidance to optimise use of telehealth. 24 Parents described the impact that delays and cancellations had to their child's health and developmental progress, with access to community care particularly problematic. A number of parents highlighted the distress caused by feelings of being abandoned by healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…Service providers must now actively engage with the rapidly evolving technology, such as use of remote stethoscopes, 23 understand barriers and support access to technology, 21 and develop appointment-specific telehealth guidance to optimise use of telehealth. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Malandraki et al [ 21 ] stated that in remote training, the viscosity and amount of food to be tried needs to be carefully selected. Since assessments are performed on patients of various severities and diseases, it is necessary to obtain consensus among experts who are candidates for telemedicine on the amount and viscosity of food and water when conducting assessments remotely.…”
Section: Introductionmentioning
confidence: 99%